Detection of Ovine Pulmonary Adenocarcinoma (OPA) in sheep from district Budgam, Jammu and Kashmir, India - MUBASHIR ALI RATHER; KHALID BASHIR; JAVAID AHMAD BABA; IMRAN BASHIR; RAKHSHAN JEELANI (Indian Journal of Animal Sciences)
An outbreak of Ovine Pulmonary Adenocarcinoma (OPA) ensued in a flock of Merino sheep in Temperate western sub zone of lesser Himalayas in Pir Panjal region of Jammu and Kashmir, India. The affected animals exhibited symptoms of labored breathing, copious bronchial discharge on elevating hindquarter and moist lung sounds. Despite treatment, all affected animals succumbed, indicating a 100% case fatality rate with higher prevalence in male (12/16) than female (4/16) and most of the deaths in spring and summer at Highland pasture (13/16) than in winter (3/16), indicating exercise intolerance. A comprehensive diagnostic approach was employed incorporating pathological, histopathological and hemi-nested PCR technique, to confirm the presence of Jaagsiekte sheep retrovirus (JSRV), the etiological agent responsible for Ovine Pulmonary Adenocarcinoma (OPA). The study reports the first confirmed natural case of OPA in Jammu and Kashmir, India, with a prevalence of 1.67% in the affected flock. The findings suggest that young sheep can be infected through colostrum and milk from carrier dam. The JSRV was confirmed by PCR techniques with Post-mortem examination revealed typical gross lesions and histopathological findings, including papillomatous ingrowths and hyperplasia of bronchial epithelium and type 2 pneumocyte proliferation.